Enhancing Geriatric Care through Speech-Language Therapy - Practical Tools for Cognitive - Communication Disorders - Szűcs; Dajana; Virág; Gadó (Magyar Gerontológia, 2025)
This study aims to present the significance of cognitive-communication disorders (CCD) in geriatric care and to highlight the role of speech therapy along with the latest research directions in diagnostics and therapeutic interventions.